Financial Management From an Emerging Market Perspective 2018
DOI: 10.5772/intechopen.72297
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Governance and Financial Performance in the Emerging Markets: Do ADRs Perform any Better than Non-Cross-Listed Firms?

Abstract: We investigate the impact governance standards have on financial performance of firms operating across various political and socioeconomic regimes. Specifically, we examine the performance of non-cross-listed emerging market firms that implement corporate governance standards similar to those mandated of firms listed on US exchanges. Using cross-sectional time-series analysis, we find that a more rigorous corporate governance structure is associated with better performance (as measured by return on assets (ROA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…It also protects the shareholders (Sheikh et al, 2018) and increases trust among stakeholders (Srairi, 2015). Sayari and Marcum (2017) and Chazi et al (2018) showed that governance leads to the good financial performance because it minimizes the internal risk and enhances the resilience of institutions to external stakeholders. Agency theory proposes that governance refers to reduce in the agency costs and consequently it improves the governance, disclosure and financial performance (Fama and Jensen, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…It also protects the shareholders (Sheikh et al, 2018) and increases trust among stakeholders (Srairi, 2015). Sayari and Marcum (2017) and Chazi et al (2018) showed that governance leads to the good financial performance because it minimizes the internal risk and enhances the resilience of institutions to external stakeholders. Agency theory proposes that governance refers to reduce in the agency costs and consequently it improves the governance, disclosure and financial performance (Fama and Jensen, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…A variety of definitions have been offered to characterize financial management, for instance [16] describes financial management as the acquisition and use of financial resources and protection of equity capital from various sources of risk. Beside, financial management in the agriculture is defined as the economic study of the acquisition and use of capital in agriculture [17]. The overall task of the financial management is to improve financial performance by ensuring that the capital structure, budgeting and budgetary control, working capital management, and financial record keeping; all these components are important for all enterprises to be powerful financially [17][18][19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Beside, financial management in the agriculture is defined as the economic study of the acquisition and use of capital in agriculture [17]. The overall task of the financial management is to improve financial performance by ensuring that the capital structure, budgeting and budgetary control, working capital management, and financial record keeping; all these components are important for all enterprises to be powerful financially [17][18][19].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Corporate governance codes are better followed in developed countries and more rigorous corporate governance structure is linked with better operating (Sayari and Marcum, 2018). In developed countries, board meeting and female representation on board have significant positive.…”
Section: Corporate Governance (Cg) and Corporate Performance (Cp)mentioning
confidence: 99%